2010
DOI: 10.1021/jp905879n
|View full text |Cite
|
Sign up to set email alerts
|

Permittivity, Conductivity, Elasticity, and Viscosity Measurements in the Nematic Phase of a Bent-Core Liquid Crystal

Abstract: We report on measurements of dielectric permittivity epsilon, electrical conductivity sigma, elastic moduli k(ii), and rotational viscosity gamma for a bent-core nematic liquid crystal. The static permittivity anisotropy epsilon(a) = epsilon(parallel)-epsilon(perpendicular) is negative; at a given temperature in the interval 107-123 degrees C, epsilon(parallel) shows two relaxations falling in the frequency bands 20-200 kHz and 0.9-2 MHz; epsilon(perpendicular) also shows a relaxation between 0.9 and 5 MHz. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 28 publications
7
66
2
Order By: Relevance
“…This is common behaviour and has been observed in many calamitic and bent-core NLCs, though the values for compound 1 are higher than those for other bent-core NLCs which typically exhibit values between B3-9 pN. 17 found K 33 B 0.9 pN at T À T NI = À2 K in a chloro-substituted material while Tadapatri et al 11 reported strong temperature 17) again exhibit a significant variation in elastic constants across even a relatively narrow nematic range. Thus, the temperature-independent behaviour in both compounds 1 and 2 is unusual and of significant interest.…”
Section: The Pure Material Compound 1: Comparison Of Measurements Anmentioning
confidence: 65%
“…This is common behaviour and has been observed in many calamitic and bent-core NLCs, though the values for compound 1 are higher than those for other bent-core NLCs which typically exhibit values between B3-9 pN. 17 found K 33 B 0.9 pN at T À T NI = À2 K in a chloro-substituted material while Tadapatri et al 11 reported strong temperature 17) again exhibit a significant variation in elastic constants across even a relatively narrow nematic range. Thus, the temperature-independent behaviour in both compounds 1 and 2 is unusual and of significant interest.…”
Section: The Pure Material Compound 1: Comparison Of Measurements Anmentioning
confidence: 65%
“…Similarly, rotational viscosity (g 1 ) is an order more for BCNs compared to CNs, and also the viscous relaxation appears to be a two-step process. 19,22,23 The uncommon behaviour of BCNs extends also to flexoelectric phenomena that form the subject of this paper. In both direct and converse flexoelectric ('flexo', for brevity) experiments employing flexible electrodes, a BC nematic has been found to show giant values ($nC m À1 ) for the bend flexocoefficient e b ; [24][25][26] in converse flexo-studies on BCNs using rigid electrodes, however, only conventional e b values ($pC m À1 ) have been obtained; 27,28 to resolve this discrepancy, a model of nonpolar molecular clusters showing quadrupolar flexoeffect has been advanced.…”
Section: Introductionmentioning
confidence: 85%
“…5 The relaxation in the planar and homeotropic cells can be tentatively assigned to the rotation of the molecule around its long and short molecular axis, respectively. 12 Recently Salamon et al observed more relaxations at relatively lower frequencies in the dielectric spectra of a resorcinol derivative in its nematic phase than the conventional calamitic ones 4 and some of these have been suggested to arise from a range of different conformers.…”
mentioning
confidence: 99%